Napping during the night shift and recovery after work among hospital nurses - Thaís Aparecida de Castro Palermo; Lúcia Rotenberg; Regina Célia Gollner Zeitoune; Aline Silva-Costa; Ester Paiva Souto; Rosane Härter Griep (Universidade de São Paulo, 2015)
OBJECTIVE: To analyze the association between the length of napping during the night shift and the recovery after work among nurses.METHOD: Cross-sectional epidemiological study involving 1940 nurses from 18 public hospitals in the City of Rio de Janeiro. A multidimensional and self-applied questionnaire was used with information about health, sociodemographic and occupational characteristics, health-related behaviors and housework. Multiple logistic regression was applied to identify the association, adjusted for confounding variables.RESULTS: The gross analyses showed 44%, 127% and 66% higher chances of a high level of recovery after work for nurses who sleep up to two hours, between 2.1 and 3 hours and 3.1 hours or more, respectively, when compared to the nurses who do not sleep. After adjusting for confounding variables, the association only continues significant for the group that sleeps 2.1 to 3 hours during the night shift (OR=1.79; 95%CI=1.33-2.41).CONCLUSION: The association between the length of napping and the high level of recovery after work, confirmed in the present results, can be included in the studies that aim to support more appropriate policies aimed at improving the workers' work, life and health conditions, not only in nursing, but night-shift workers in general.